Transcriptome analysis of copper stress response in rice seedling using DNA microarray - Nam, Trinh Ngoc; Vinh, Nguyen Nhat; Thia, Le Hong; Hue, Tran Do Kim (Vietnam Journal of Biotechnology, 2018)
Heavy metal contamination along with the increase in food demand are a primary concern in Vietnam and all over the world. In order to enhance crop tolerance to unfavorable cultivation conditions including heavy metal toxicity, understanding of plant response system under the effect of heavy metals is necessary. In the current study, physiological, biochemical and transcriptomic changes of rice seedings (Oryza sativa L. cv. IR64) were investigated under copper (Cu) stress. Root elongation and root fresh weight were decreased whereas accumulation of copper in root was enhanced significantly with increasing copper concentration from 2.5 to 15 M. In addition, copper induced endogenous reactive oxygen species (ROS) generation and activated isoenzymes of superoxide dismutase (SOD) and catalase (CAT). The molecular mechanism of rice roots in response to copper toxicity at mRNA expression level was analyzed by microarray technique. Functions and roles of genes were also analyzed by bioinformatic tools AgriGO and MapMan. Gene ontology analysis revealed that 1900 Cu responsive genes were involved in phytohormones, reactive oxygen species, signaling pathways, transcription factors, transport activities, antioxidant defense systems. Through phytohormones and reactive oxygen species, Cu may inhibit rice root growth. Phytohormones and reactive oxygen species can also be signal molecules in signaling pathways with the participation of mitogen-activated protein kinase (MAPK) cascades, and transcription factors in response to Cu stress. Detoxification and protection mechanisms may involve transport activities and antioxidant defense systems during Cu treatment. These results may provide new insights into mechanisms of rice plant to tolerate with Cu toxicity conditions